Institutional Complexity in Turbulent Times: Formalization, Collaboration, and the Emergence of Blended Logics - Ramus, Tommaso; Vaccaro, Antonino; Brusoni, Stefano (Academy of Management Journal, 2017)
This paper explores how organizations dealing with institutional complexity manage internal tensions triggered by environmental turbulence. Based on a longitudinal, comparative study, we extend previous research that has identified collaboration and formalization as possible mechanisms to reconcile organizational tensions in such situations. We show that neither of these mechanisms is sufficient in itself to resolve tensions. Rather, it is the structured interaction between collaboration and formalization that allows organizations to successfully blend logics and reconcile their conflicting demands. On the basis of our findings, we develop a process model that explains how organizations change in response to environmental turbulence.